The prevention and control of agriculture-associated diseases - International Livestock Research Institute (International Livestock Research Institute, 2013)
A third of the world’s population still grows their own food or buys local food in local markets. But the foods poor people grow, buy and eat often make them sick, and can even kill them. Sick people cost poor families money because treatment is expensive and sickness stops them being productive. In 2012, a research program was started to investigate the links between agriculture, nutrition and health in poor nations.